2018
DOI: 10.1093/ageing/afy025
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in physical function and physical activity in older adults

Abstract: Background physical function (PF) and physical activity (PA) both decline as adults age and have been linked to negative outcomes, including dementia, depression and cardiovascular diseases. Although declines in each are associated with numerous negative outcomes, the longitudinal relationship between these two measures is unclear. Objective to examine the dynamic, bidirectional associations between declines in PF and PA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…To our knowledge, the present study is the first to examine longitudinal trends and the annual rate of change in physical function, and the prevalence of physical function status by sex, age, race/ethnicity, and weight status, among adults aged 65 years and older using an objective measure of physical function. Similar to previous studies, [15][16][17] this study found that physical function deteriorated steadily with increasing age in both males and females. However, direct comparison of results of previous studies and the present study is challenging as most prior studies were conducted outside the United States, [15][16][17] utilized a relatively homogeneous sample with respect to race/ethnicity (95% whites), 16 or employed different physical function measures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, the present study is the first to examine longitudinal trends and the annual rate of change in physical function, and the prevalence of physical function status by sex, age, race/ethnicity, and weight status, among adults aged 65 years and older using an objective measure of physical function. Similar to previous studies, [15][16][17] this study found that physical function deteriorated steadily with increasing age in both males and females. However, direct comparison of results of previous studies and the present study is challenging as most prior studies were conducted outside the United States, [15][16][17] utilized a relatively homogeneous sample with respect to race/ethnicity (95% whites), 16 or employed different physical function measures.…”
Section: Discussionsupporting
confidence: 90%
“…However, direct comparison of results of previous studies and the present study is challenging as most prior studies were conducted outside the United States, [15][16][17] utilized a relatively homogeneous sample with respect to race/ethnicity (95% whites), 16 or employed different physical function measures. 16,17 Nonetheless, the findings of the present study indicate that physical function declines with age, regardless of race/ethnicity or weight status. While considering the minimally clinically important difference (≥0.3 points' difference for SPPB), 29 only respondents aged 75 years and older had a meaningful annual SPPB score rate of decline, which suggests aging is a more influential factor than race/ethnicity or weight status for physical function decline.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, it is also possible that an increased fat mass index is a consequence of decline in HRQoL. Older adults who have problems with functioning tend to be less physically active [51], which may, in turn, increase fat mass over time. Nevertheless, we found a prospective association between baseline fat mass index and change in HRQoL, which suggests that at least some of the association is explained by a link directed from fat mass to physical HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between physical inactivity and type 2 diabetes is well known 21) . The relationship between PA and physical function (PF) is bidirectional, with PF more consistently predicting declines of PA 22) . In a sex-specific univariate analysis, KEF was significantly higher in patients who regularly exercised than in patients who did not regularly exercise 23 ) .…”
Section: Regular Physical Activity and Physical Function In Patients mentioning
confidence: 99%